Analytical investigation on sound transmission loss of functionally graded nanocomposite cylindrical shells reinforced by carbon nanotubes. Issue 10 (3rd October 2022) - Ahmadi, Mastaneh; Talebitooti, Mostafa; Talebitooti, Roohollah
Abstract: This article presents the numerical results for acoustic transmission through relatively thick functionally graded carbon nanotube-reinforced composite (FG-CNTRC) cylindrical shells. The vibration behavior of cylindrical shell is modeled using the first-order shear deformation theory (FSDT) which takes into account the transverse shear strains averaged over the wall thickness. Effective properties of materials of the shell reinforced by single-walled carbon nanotubes (SWCNTs) are estimated through a micromechanical model based on the extended rule of mixture. Furthermore, four different types of distribution of carbon nanotubes (CNTs) along the thickness direction, i.e., UD, FG-V, FG-O, and FG-X, are considered. The shell is submerged in a fluid with an external airflow and an oblique plane wave excites on the external sidewall of the shell. In order to obtain an analytical solution of sound transmission loss (STL), the motion equations of the shell and acoustic wave equations are simultaneously solved. Then, natural frequencies and STL are extracted and they are compared with those available in the literature. Finally, the obtained results are discussed to demonstrate the effectiveness of the CNT distribution, volume fraction of CNTs, shell thickness, and Mach number on STL.